Hubungan Tingkat Neurotisme dengan Fear of Missing Out (FoMO) pada Remaja Pengguna Aktif Media Sosial - Christina, Riska; Yuniardi, Muhammad Salis; Prabowo, Adhyatman (Indigenous, 2019)
The massive flow of easily-accessed information in social media has affected teenagers with a high level of neuroticism hard to control their behavior in using social media. As a consequence, they are prone to experience anxiety that other people are engaging in some more fun and valuable activities and that they miss the chance to engage in those activities. This anxiety is known as “Fear of Missing Out (FoMO)”. This study aimed to investigate the correlation between neuroticism and the Fear of Missing Out among teenagers who actively use social media. This study used a correlational study design with purposive sampling. Subjects of this study were teenagers with a total of 110 between the age of 13-18 that actively use social media in recent months. The instrument used were the Big Five Inventory (BFI) and modified Fear of Missing Out (FoMO) Scale. Data were analyzed using the Pearson Product Moment. Correlation results showed that there was a significant positive correlation between neuroticism and Fear of Missing out (FoMO) scores among teenagers. Coefficient value of the correlation (r) was 0,464 with p = 0,00 0,01. It can be concluded, the higher the tendency of the teenagers having neuroticism, the higher risk of experiencing anxiety that other people’s activities are more fun and valuable. The contribution of the neuroticism to the Fear of Missing Out (FoMO) was 21,5%.